Program one day one story dalam membangun karakter dan spiritual siswa SDN 03 Cijambe - Rosa Shafa Kamila; Syafrudin Syafrudin; Nurhasanah Nurhasanah (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2026)
This study aims to analyze the implementation of the hidden curriculum through the One Day One Story program in developing character and enhancing the spiritual intelligence of students at SDN 03 Cijambe. Using a qualitative case study approach, data were collected from teachers and students in grades IV–VI through observations, interviews, and documentation. The findings show that the program serves as a medium for self-reflection, helping students understand their experiences, manage emotions, and improve self-awareness. It also facilitates the internalization of character values such as honesty, empathy, and responsibility, while strengthening spiritual intelligence through regular reflective writing and teacher guidance. The study suggests that reflective writing can be an effective hidden curriculum strategy for character development and spiritual intelligence enhancement among elementary school students.